The day of the gamer - Vink, Amanda (Power Coders., 2019)
The members of the Coding Club are preparing to submit their newest computer game to the All-State Gaming Competition. But when an important component of their game--a graphic novel they've worked with a fellow student to create--goes missing, the teens will have to think fast before they miss out on the competition all together.